MODEL PEMBELAJARAN DISCOVERI LEARNING TERINTEGRASI SOFTWARE GEOGEBRA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD - Pupu Maspuroh; Awatif; Sugeng Riyadi (Hira Institute, 2026)
Low mathematics learning outcomes remain a major issue in elemtary schools, primarily due to the dominance of conventional teaching methods and the limited use of tecnology in the learning process. This study aims to improve studens mathematics learning outscome though the implementation of the Discovery Learning model integrated with the Geogebra Software. The reserch employed a Classroom Actions Reserrch (CAR) design conducted in to cycles. Each cycles consisted of three meetings. Two sessions for intructional activities and one session for a learning outcom test. The reserch subjects were 25 fifth-grade elementary school students. The results revealed improvement in students learning outcomes, with a learning mastery rate of 68% and average score of 71.6 in the first cycle, which increased to 88% mastery and an average score of 80 in the second cycle. These findings indicate that yhe integration of the Discovery Learning model with Geogebra Software is effective in enchaching students mathematics learning outcomes. Therefore, this model is recommended as an inovative instuction strategy to srengthen conceptual understanding an improve academic achievement in mathematics at the elementary school level.